Hemodynamic response function abnormalities in schizophrenia during a multisensory detection task. Issue 2 (24th November 2015) - Hanlon, Faith M.; Shaff, Nicholas A.; Dodd, Andrew B.; Ling, Josef M.; Bustillo, Juan R.; Abbott, Christopher C.; Stromberg, Shannon F.; Abrams, Swala; Lin, Denise S.; Mayer, Andrew R.
Abstract: Functional magnetic resonance imaging (fMRI) of the blood oxygen level dependent (BOLD) response has commonly been used to investigate the neuropathology underlying cognitive and sensory deficits in patients with schizophrenia (SP) by examining the positive phase of the BOLD response, assuming a fixed shape for the hemodynamic response function (HRF). However, the individual phases (positive and post‐stimulus undershoot (PSU)) of the HRF may be differentially affected by a variety of underlying pathologies. The current experiment used a multisensory detection task with a rapid event‐related fMRI paradigm to investigate both the positive and PSU phases of the HRF in SP and healthy controls (HC). Behavioral results indicated no significant group differences during task performance. Analyses that examined the shape of the HRF indicated two distinct group differences. First, SP exhibited a reduced and/or prolonged PSU following normal task‐related positive BOLD activation in secondary auditory and visual sensory areas relative to HC. Second, SP did not show task‐induced deactivation in the anterior node of the default‐mode network (aDMN) relative to HC. In contrast, when performing traditional analyses that focus on the positive phase, there were no group differences. Interestingly, the magnitude of the PSU in secondary auditory and visual areas was positively associated with the magnitude of task‐induced deactivation within the aDMN, suggesting a possible common neural mechanism underlying both of these abnormalities (failure in neural inhibition). Results are consistent with recent views that separate neural processes underlie the two phases of the HRF and that they are differentially affected in SP. Hum Brain Mapp 37:745–755, 2016 . ©2015 Wiley Periodicals, Inc.